2012
DOI: 10.1509/jm.09.0581
|View full text |Cite
|
Sign up to set email alerts
|

Belief in a Just World: Consumer Intentions and Behaviors toward Ethical Products

Abstract: This is the published version of the paper.This version of the publication may differ from the final published version. Although consumers report positive attitudes toward ethical goods, their intentions and behaviors often do not follow suit. Just-world theory highlights the conditions under which consumers are most likely to prefer fair-trade products. This theory proposes that people are motivated to construe the world as a just place where people get what they deserve. In the current research, when people … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
215
4
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 220 publications
(228 citation statements)
references
References 62 publications
8
215
4
1
Order By: Relevance
“…Whereas those respondents who did not believe that corporate donations can make a change toward more justice in the world stated that they did not very much care about a company's engagement in poor countries, those who said they believed in a justice restoration potential reported that they had frequently bought products that are linked to donations to poorer countries. This result directly ties in with the results of White et al (2012), who find that customers who believe in a justice restoration potential of corporate actions are more likely to purchase fair trade products.…”
Section: Justice Restoration Potentialsupporting
confidence: 69%
See 4 more Smart Citations
“…Whereas those respondents who did not believe that corporate donations can make a change toward more justice in the world stated that they did not very much care about a company's engagement in poor countries, those who said they believed in a justice restoration potential reported that they had frequently bought products that are linked to donations to poorer countries. This result directly ties in with the results of White et al (2012), who find that customers who believe in a justice restoration potential of corporate actions are more likely to purchase fair trade products.…”
Section: Justice Restoration Potentialsupporting
confidence: 69%
“…In line with the literature on whether corporate actors have the potential to restore global justice (White et al 2012), discussions encompassed this aspect in all three focus groups, and in all groups, the subject of a justice restoration potential emerged naturally from the participants' own comments (i.e., before the interviewer could raise justice restoration potential issues). The respondents discussed whether MNCs really have the potential to change the predicaments of the inhabitants of the poorer parts of the world.…”
Section: Justice Restoration Potentialmentioning
confidence: 82%
See 3 more Smart Citations